The blue halite in Morsleben, Germany: a natural lyoluminescence dosimeter? - Biernacka, Magdalena; Majgier, Renata; Staninski, Krzysztof; Kaczmarek, Małgorzata; Zelek-Pogudz, Sylwia; Sądel, Michał; Szufa, Katarzyna M.; Blanke, Hartmut; Kreutzer, Sebastian (Journal of luminescence, 2025)
The potential of salt as an artificial and natural luminescence dosimeter is well documented in the literature. However, the potential of lyoluminescence, i.e., luminescence during salt dissolution, was neglected over time, and the first attempts to use LL as a natural dosimeter were not followed up on further. In this study, we build upon previous studies and investigate the LL properties of a sylvite vein containing blue halite from the salt repository Morsleben (Germany) and attempt to determine the timing of its last crystallization. We employed four experimental setups optimized for LL detection and present measurements using a high-sensitive CCD camera and photon counting heads to detect and prove the existence of natural LL signals in blue halite and sylvite. An enhanced LL signal was used to estimate the equivalent dose using an additive dose approach. Additional UV-VIS spectroscopy determined colour centres in the studied minerals towards a better understanding of the underlying LL mechanism. Our results indicate that the LL age underestimates the actual crystallization event of the old geological minerals in the repository due to long-term exposure to ionizing radiation. However, we are optimistic that the LL is a promising tool for dating the last crystallization event of certain minerals for younger repositories, where the exposure time was shorter.
Online veröffentlicht: 27. Januar 2025, Artikelversion: 31. Januar 2025
Gesehen am 01.04.2025